Creatine and its application as an ergogenic aid - Greenhaff, P. L. (International Journal of Sport Nutrition and Exercise Metabolism, 1995)
Phosphocreatine (PCr) availability is likely lo limit performance in brief, high-power exercise because the depletion of PCr results in an inability to maintain adenosine triphosphate (ATP) resynthesis al the rate required. It is now known that the daily ingestion of four 5 gram doses of creatine for 5 days will significantly increase intramuscular and PCr concentrations prior to exercise and will facilitate PCr resynthesis during recovery from exercise, particularly in those individuals with relatively low creatine concentrations prior to feeding. As a consequence of creatine ingestion work output during repeated bouts of high-power exercise has been increased under a variety of experimental conditions. The reduced accumulation of ammonia and hypoxanthine in plasma and the attenuation of muscle ATP degradation after creatine feeding suggest that the ergogenic effect of creatine is achieved by better maintaining ATP turnover during contraction. (Greenhaff reviews the role of cr eatine in muscle energy metabolism and fatigue, the effect of creatine ingestion on muscle creatine concentration, practical applications, and concludes with the following:) In conclusion, research concerned with the effects of creatine ingestion on muschle function and metabolism during exercise in healthy normal individuals and in disease states is in its infancy but is sure to progress rapidly. Recent findings indicate that it is important ot optimize tissue creatine uptake in order to maximize performance benefits. Creatine should not be viewed as another gimmick supplement: its ingestion is a means of providing immediate, significant performance improvements to athletes involved in explosive sports. In the long run, creatine may also allow athletes to train without fatigue at an intensity higher than that to which they are accustomed. For these reasons alone, creatine supplementation could be viewed as a significant development in sport nutrition.